TVD‐PB logic circuit based on camouflaging circuit for IoT security. Issue 1 (22nd April 2021) - Zhang, Yuejun; Wu, Qiufeng; Wang, Pengjun; Wen, Liang; Luan, Zhicun; Gu, Chongyan
Abstract: Internet of Things (IoT) devices are vulnerable to many physical attacks, including reverse engineering and side‐channel analysis because the sensitive information of circuits may be leaked through the physical characteristics of the device. A logic camouflaging circuit is proposed that uses a balanced power consumption and threshold voltage‐defined technique to provide an antiphysical attack scheme to protect the hardware security for IoT devices. The proposed circuit uses a symmetric differential pull‐down network in implementing the different logic functions through the threshold voltage reconfiguration circuit. As a result, the power consumption of the circuit attains balance and stability between two different logical operations. The proposed threshold voltage‐defined power‐balance (TVD‐PB) design is fabricated using a 65‐nm CMOS technology, and the core area occupies approximately 0.0044 mm 2, composed of NAND, NOR, XOR, and INV components and multiplier gates of the proposed TVD‐PB circuit. The entire chip passed the logic function tests. The measured results show that the average similarity of the TVD‐PB universal gate is 99.68%. In addition, the current margin is higher than 55 μA and power consumption of 0.455 mW during each clock cycle at 1.2 V derives 0.1072% of the normalized energy deviation and 0.0453% of the normalized standard deviation. Compared with other state‐of‐the‐art techniques, the power dependency against power attacks is improved effectively.